2023
DOI: 10.1007/s11356-023-26333-6
|View full text |Cite
|
Sign up to set email alerts
|

When will China’s industrial carbon emissions peak? Evidence from machine learning

Abstract: The manufacture of products in the industrial sector is the principal source of carbon emissions. To slow the progression of global warming and advance low-carbon economic development, it is essential to develop methods for accurately predicting carbon emissions from industrial sources and imposing reasonable controls on those emissions. We select a support vector machine to predict industrial carbon emissions from 2021 to 2040 by comparing the predictive power of the BP (backpropagation) neural network and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In this study, we used balanced panel data from 270 Chinese cities from 2005 to 2020 as a research object: (1) to show the spatio-temporal evolution pattern of urban industrial carbon emission efficiency; (2) to analyze the aggregation characteristics of industrial carbon emission efficiency in Chinese cities using the Global Moran's I statistic; and (3) to use the hierarchical regression model for panel data to explore the non-linear impact of the digital economy on the industrial carbon emission efficiency of cities. The main conclusions are as follows: The regression coefficient of population size is positive, so the regression coefficient increases and then decreases with the increase in quartiles, with a positive effect on the enhancement of urban industrial carbon emission efficiency in the middle quartile and more obvious inhibitory effects in the low and high quartiles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we used balanced panel data from 270 Chinese cities from 2005 to 2020 as a research object: (1) to show the spatio-temporal evolution pattern of urban industrial carbon emission efficiency; (2) to analyze the aggregation characteristics of industrial carbon emission efficiency in Chinese cities using the Global Moran's I statistic; and (3) to use the hierarchical regression model for panel data to explore the non-linear impact of the digital economy on the industrial carbon emission efficiency of cities. The main conclusions are as follows: The regression coefficient of population size is positive, so the regression coefficient increases and then decreases with the increase in quartiles, with a positive effect on the enhancement of urban industrial carbon emission efficiency in the middle quartile and more obvious inhibitory effects in the low and high quartiles.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used balanced panel data from 270 Chinese cities from 2005 to 2020 as a research object: (1) to show the spatio-temporal evolution pattern of urban industrial carbon emission efficiency; (2) to analyze the aggregation characteristics of industrial carbon emission efficiency in Chinese cities using the Global Moran's I statistic; and (3) to use the hierarchical regression model for panel data to explore the non-linear impact of the digital economy on the industrial carbon emission efficiency of cities. The main conclusions are as follows:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BP neural network, put forward by scholars such as Rinehart and MeClelland, is the most widely used artificial neural network [37], which has the characteristics of self-learning adaptation, parallel processing, strong learning ability and generalization [38], and generally consists of an input layer, hidden layer and output layer. Studies have shown that a three-layer BP neural network prediction model can approximate any nonlinear function [39,40].…”
Section: Bp Neural Network Modelmentioning
confidence: 99%